THE EFFECTIVENESS USING COOPERATIVE NUMBERED HEADS TOGETHER AND TWO STAY TWO STRAY TYPE LEARNING MODEL ON STUDENT’S MATHEMATIC LEARNING AT SMP - Aji Nurcahyo; Uus Kusdinar (Universitas Ahmad Dahlan, 2018)
The nature of learning that still tends to be teacher-centered. This is what is thought to lead to poor learning outcomes. Need a learning model to improve learning in the classroom to obtain satisfactory learning outcomes. This study aims to determine the effectiveness of the use of cooperative learning model between Numbered Heads Together (NHT) with Two Stay Two Stray (TS - TS) on the learning outcomes of VII students of State Junior High School (SMP Negeri) 3 Jetis Bantul Yogyakarta academic year 2014/2015 on the principle of linear equations one variable and equivalents. This type of research is a comparative study. This research uses a posttest - only control design. The population in this study were all students of class VII, namely class VII A, VII B, VII C, VII D, and VII E, consisting of 160 students. The research sampling technique used random sampling: the entire population consisting of five classes is randomized. In one class for the trial, class VII D, and Class VII A and VII B as the research sample. The research data was collected by using the posttest problem to know the learning result. Data analysis for hypothesis testing in this research using a two-party t-test and one party t-test with a 5% significance level. Based on the calculation of two-t-test on the research with a significant level of 5% = 0.05 and dk = 62 obtained and which mean then there are differences in mathematics learning outcomes using NHT type cooperative learning method and TS-TS type cooperative learning. Then based on the hypothesis test, one party with significant level 5% = 0,05 and dk = 62 obtained and which mean the cooperative learning model of NHT type is more effective than the TS-TS model of cooperative learning model of the mathematics learning outcomes of grade VII students of SMP Negeri 3 Jetis academic year 2014/2015 on the subject of linear equations of one variable and the equivalence.